2017
DOI: 10.1038/s41598-017-08992-x
|View full text |Cite
|
Sign up to set email alerts
|

Colossal permittivity behavior and its origin in rutile (Mg1/3Ta2/3)xTi1-xO2

Abstract: This work investigates the synthesis, chemical composition, defect structures and associated dielectric properties of (Mg2+, Ta5+) co-doped rutile TiO2 polycrystalline ceramics with nominal compositions of (Mg2+ 1/3Ta5+ 2/3)xTi1−xO2. Colossal permittivity (>7000) with a low dielectric loss (e.g. 0.002 at 1 kHz) across a broad frequency/temperature range can be achieved at x = 0.5% after careful optimization of process conditions. Both experimental and theoretical evidence indicates such a colossal permittivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 48 publications
3
45
1
6
Order By: Relevance
“…Our recent work on the development of highly efficient TiO 2 ‐based VLCs demonstrated the significance of introducing a high but equal concentration of (N 3− , Nb 5+ ) defect pairs for outstanding photocatalytic properties ,. This, in combination with our previous research on (In 3+ , Nb 5+ ), (Al 3+ , Nb 5+ ), (Mg 2+ , Ta 5+ ), (Zn 2+ , Nb 5+ ) and (In 3+ , Ta 5+ ) co‐doped rutile/anatase TiO 2 ceramics/nanocrystals, suggests the complexity of ionic co‐doping in structurally strongly correlated oxides. The introduced extrinsic ions may stay as isolated point defects in host materials and may also form defect‐pairs or clusters coupled with the host ions and local crystal structures.…”
Section: Figuresupporting
confidence: 82%
“…Our recent work on the development of highly efficient TiO 2 ‐based VLCs demonstrated the significance of introducing a high but equal concentration of (N 3− , Nb 5+ ) defect pairs for outstanding photocatalytic properties ,. This, in combination with our previous research on (In 3+ , Nb 5+ ), (Al 3+ , Nb 5+ ), (Mg 2+ , Ta 5+ ), (Zn 2+ , Nb 5+ ) and (In 3+ , Ta 5+ ) co‐doped rutile/anatase TiO 2 ceramics/nanocrystals, suggests the complexity of ionic co‐doping in structurally strongly correlated oxides. The introduced extrinsic ions may stay as isolated point defects in host materials and may also form defect‐pairs or clusters coupled with the host ions and local crystal structures.…”
Section: Figuresupporting
confidence: 82%
“…Thus, multiple Debye‐type relaxations with different τ overlapped each other and show a broad distribution of τ . Different τ resulted in α > 0 when x = 0 . In the rutile INZT ( x > 0) solid solution, Zr 4+ replaces Ti 4+ , which affects the states of localized electrons.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, giant permittivity materials with a large dielectric constant ( ε r ), low dielectric loss (tanδ), and good thermal stability have attracted much attention due to the requirements for the miniaturization of electronic devices and high‐energy storage capacitors . In 2013, the remarkable dielectric behavior of the materials, In and Nb codoped TiO 2 ‐based ceramics, was reported by Liu et al; these materials showed low dielectric loss (<5%) and large dielectric constant (~10 4 ) and had better temperature stability in the range from 80 to 450 K. Meanwhile, the authors deemed that the origin of the dielectric response was attributed to the intrinsic dielectric effect, that is, the electron pinned defect dipole (EPDD).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the remarkable dielectric behavior of the materials, In and Nb codoped TiO 2 ‐based ceramics, was reported by Liu et al; these materials showed low dielectric loss (<5%) and large dielectric constant (~10 4 ) and had better temperature stability in the range from 80 to 450 K. Meanwhile, the authors deemed that the origin of the dielectric response was attributed to the intrinsic dielectric effect, that is, the electron pinned defect dipole (EPDD). Subsequently, based on the same design idea, a series of codoped TiO 2 ‐based ceramics with better dielectric properties were also obtained for other ions (Ca 2+ , Zn 2+ , Mg 2+ , Sc 3+ , Y 3+ , Al 3+ , In 3+ , Yb 3+ , etc., as acceptors and Nb 5+ , Ta 5+ , etc., as donors) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation